SUPPLY CHAIN MANAGEMENT IN MR. ARPEN'S SALTED FISH BUSINESS IN BONTOSI VILLAGE, LABOBO SUB-DISTRICT, BANGGAI LAUT DISTRICT - Umbasene, Elis Elviana; Miru, Sulaeman; Asngadi, Asngadi (Master of Management Study Program, Faculty of Economics and Business, Tadulako University, 2024)
The purpose of this study is to identify and analyze the supply chain model used in Mr. Arpen's salted fish business in Bontosi Village, Labobo District, Banggai Laut Regency. This research was conducted over the span of one month using a descriptive qualitative method with a survey approach. Data were collected through in-depth interviews with selected informants relevant to the study. The analysis was carried out using descriptive techniques based on supply chain analysis. The results revealed four types of supply chain models in Mr. Arpen's salted fish business. The first model involves fishermen, Mr. Arpen, and consumers. The second model includes fishermen, fish collectors, Mr. Arpen, retailers, and consumers. The third model consists of fishermen, fish collectors, Mr. Arpen, distributors, and consumers. The fourth model comprises fishermen, fish collectors, Mr. Arpen, distributors, retailers, and finally consumers.